2010
DOI: 10.1002/jclp.20726
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of a brief measure of perceived burdensomeness and thwarted belongingness for the detection of suicidal military personnel

Abstract: Perceived burdensomeness (PB) and thwarted belongingness (TB) are important indicators of suicide risk; however, limited research has investigated applicability to military populations, and no efforts have been initiated to translate these constructs into easily implemented clinical tools. The current study examined the structure and validity of a brief self-report survey of PB and TB, the 10-item Interpersonal Needs Questionnaire (INQ-10), among a sample of 219 deployed military personnel. Factor analysis con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
82
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 29 publications
(17 reference statements)
11
82
1
1
Order By: Relevance
“…These constructs, which are part of the Interpersonal Psychological Theory, were measured with the 10-item version of the Interpersonal Needs Questionnaire (INQ; Bryan, 2011;Hill et al, 2014;Van Orden, Witte, Gordon, Bender, & Joiner, 2008). The INQ was designed to measure participants' beliefs about the extent to which they feel connected to others (i.e., belongingness) and the degree to which they feel they are a burden to others (i.e., burdensomeness).…”
Section: Methodsmentioning
confidence: 99%
“…These constructs, which are part of the Interpersonal Psychological Theory, were measured with the 10-item version of the Interpersonal Needs Questionnaire (INQ; Bryan, 2011;Hill et al, 2014;Van Orden, Witte, Gordon, Bender, & Joiner, 2008). The INQ was designed to measure participants' beliefs about the extent to which they feel connected to others (i.e., belongingness) and the degree to which they feel they are a burden to others (i.e., burdensomeness).…”
Section: Methodsmentioning
confidence: 99%
“…6 Only 1 study included people who were identified as clinically suicidal 7 (29 elderly people who have contemplated suicide recruited from mental health inand outpatient facilities). The other studies have been done using community samples or populations of US college students.…”
Section: Study Populationsmentioning
confidence: 99%
“…Previous studies have found utility for such a brief screening of suicidality as done in this study (Bryan, 2011;, and the findings of the current study suggest that screening military personnel and veterans for facets of IPT in addition to overt suicidal behavior may continue to be important. Further, for those service members or veterans who present in clinical settings and are assessed as having elevated suicide risk, the facets of IPT provide important areas to work on improving for the individual.…”
Section: Discussionmentioning
confidence: 71%
“…Thwarted belongingness is applicable to individuals who genuinely lack social support networks, as well as individuals who have contact with family and friends but feel that they are not genuinely connected to them. Thwarted belongingness has been found to be associated with suicidal ideation in military samples (Bryan, 2011). It has also been found to be a common theme in suicide notes left by military personal who died by suicide (Cox et al, 2011).…”
mentioning
confidence: 98%